Peran Good Corporate Governance dalam Mencegah Korupsi dan Penyalahgunaan Wewenang - Amelia, Lia; Erry Sunarya; Tuah Nur (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Good Corporate Governance (GCG) plays a very important role in creating a transparent, accountable and integrity corporate environment. One of the main objectives of implementing GCG is to prevent corrupt practices and abuse of authority that can harm the company and society. This article discusses how GCG principles, such as transparency, accountability, clear division of authority, and anti-corruption policies, can reduce the risk of unethical actions in organizations. In addition, the role of effective internal and external controls is also key in detecting and preventing abuse of authority. By consistently implementing GCG, companies can enhance their reputation, strengthen stakeholder trust, and maintain corporate sustainability. Through leadership with integrity and a corporate culture that prioritizes ethics, GCG is expected to create a business environment that is clean and free from corruption. This study aims to describe the role of GCG in preventing corruption and abuse of power and provide recommendations to strengthen GCG implementation in Indonesian companies.